Non-invasive electrical and magnetic stimulation of the brain, spinal cord, roots and peripheral nerves: Basic principles and procedures for routine clinical and research application. An updated report from an I.F.C.N. Committee. Issue 6 (June 2015) - Rossini, P.M.; Burke, D.; Chen, R.; Cohen, L.G.; Daskalakis, Z.; Di Iorio, R.; Di Lazzaro, V.; Ferreri, F.; Fitzgerald, P.B.; George, M.S.; Hallett, M.; Lefaucheur, J.P.; et al.
Highlights This review is an up-date document on basic aspects of non-invasive stimulation of brain, spinal cord and nerve roots. The main physiological, theoretical and methodological features of transcranial magnetic stimulation (TMS) are described. Instructions for practical use of non-invasive stimulation in clinical applications and research are provided.